2013
DOI: 10.1007/s40415-013-0021-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of the structure of epiphytic algal community on different substrates from a Neotropical floodplain

Abstract: This study aimed at analyzing the structure of epiphytic algal community on aquatic macrophytes morphologically different and in distinct hydrological periods at a lentic environment (Pombas Lake) located in the Upper Paraná River floodplain. In this study we tested the hypothesis that epiphyton richness, diversity, density, and composition, associated with submerged macrophytes are affected by hydrological dynamics and by habitat heterogeneity. The macrophytes used as substrates were Eichhornia azurea Kunth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In this study, Biolo and Rodrigues (2013) showed no significant differences reported in the mean values of specific richness between the same substrates, only for sampled periods and for interaction "time x substrate"; and significant differences between periphytic algae from distinct substrates were registered only for average values of density. Furthermore, Neif et al (2013) also found no significant differences in the species composition and richness of periphytic algae of different submerged macrophytes at the same floodplain, including the attribute density, but only between periods. Our study provides first steps for understanding comparative structure of periphytic algal communities in E. azurea, N. amazonum and O. cubense.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In this study, Biolo and Rodrigues (2013) showed no significant differences reported in the mean values of specific richness between the same substrates, only for sampled periods and for interaction "time x substrate"; and significant differences between periphytic algae from distinct substrates were registered only for average values of density. Furthermore, Neif et al (2013) also found no significant differences in the species composition and richness of periphytic algae of different submerged macrophytes at the same floodplain, including the attribute density, but only between periods. Our study provides first steps for understanding comparative structure of periphytic algal communities in E. azurea, N. amazonum and O. cubense.…”
Section: Discussionmentioning
confidence: 79%
“…Richness of taxa in this region is very low, with only 26 taxa recorded by these authors. At the upper portion of the floodplain, Neif et al (2013) analyzed the periphyton structure from two macrophytes, E. azurea and Egeria najas Planch -of a lake, both submerged macrophytes. Regarding macrophytes covered in the present study, Nymphaea amazonum Martius & Zuccarini and Oxycaryum cubense (Poeppig and Kunth) Lye, knowledge of the composition and similarity of periphyton is still scarce, with previous data published related to the specific richness and density of periphytic communities in these macrophytes (Biolo and Rodrigues, 2013) as part of the major project which originated this study.…”
Section: Introductionmentioning
confidence: 99%